The Influence of Current Ratio, Total Asset Turnover, Return on Assets, Company Size and Debt to Equity on Profit Growth in Property and Real Estate Companies Listed on the Indonesian Stock Exchange for the 2016 - 2020 Period - Putri Wulandari; Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The purpose of this study was to analyze the effect of the Current Ratio (CR), Total Assets Turnover (TATO), Return On Assets (ROA), Company Size (SIZE), and Debt to Equity Ratio on Profit Growth in Property and Real Estate Companies during the period 2016-2020. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. Sampling was carried out by purposive sampling consisting of 15 companies. The data collection technique used is documentation. By using the Eviews 9 program, the research data were analyzed using a panel data regression approach with a significance level of 0.05. This analysis shows that the variables CR, TATO and ROA have a positive and significant effect on Profit Growth. Meanwhile, Company Size (SIZE) has a negative and significant effect on Profit Growth and DER has a positive and insignificant effect on Profit Growth.